PROGRAM AKSI DESA MANDIRI PANGAN DAN KETAHANAN PANGAN RUMAH TANGGA DI KABUPATEN BATANG - Eny Hari Widowati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
Independent Food Village program is a strategic activity to achieve food security of rural region. “Food Village program” activities in Batang were implemented in the Tulis District, Siberuk Village, and in 2008 on the stage of development as well as yet unknown effect on household food security in implementing the program. The Purpose of this study was to analyze the influence of independent village food action programs and the factors affecting food security of the household. Research was conducted with quantitative methods, based on the questionnaire to guide the interview. This study involved 20 respondents, consisting of three affinity groups: productive economic groups, the means of production, and husbandry. The effect of “Food Village program”was analyzed descriptivel;, household food availability is calculated referring to the level of adequacy of food availability for 2200 calories /capita/day, measured in purchasing power of household purchasing power of food sourced from revenue activities “Food Village program” over the last month. Consumption of food was analyzed by looking at the size of food quality; Food distribution was analyzed by knowing the availability of food in quantity by quality, time and quality are right, The degree of household food security was measured two indicators of food security, namely purchasing power and adequacy of energy consumption. Food security action program contributes revenue to the group the means of production of 16.61%, with high purchasing power so that the availability of food in high numbers, quality and safe for consumption so that household food stand in conditions guaranteed. Productive economic groups contributed 13.22% of income, with low food availability and purchasing power in a timely manner as well as safe to eat, so that households have less food. Husbandry groups contributed revenues of 4.28% with low food availability and low purchasing power so that difficulties in obtaining food and causes of household food insecurity conditions.